Income Inequality and the Well‐Being of American Families. Issue 3 (6th June 2019) - Duncan, Greg; Magnuson, Katherine; Murnane, Richard; Votruba‐Drzal, Elizabeth
Abstract : Income inequality has increased steadily over the past 40 years. We briefly review the nature and causes of this increase and show that income‐based gaps in children's academic achievement and attainment grew as well. To probe whether the increasing income gaps may have played a role in producing the growing achievement and attainment gaps, we summarize the evidence for the effect of family income on children, paying particular attention to the strength of the evidence and the timing of economic deprivation. We show that, in contrast to the nearly universal associations between poverty and children's outcomes as reported in the correlational literature, evidence from social experiments and quasi experiments shows impacts on some domains of child functioning but not others. At the same time, we have no experimental evidence on how economic deprivation affects children in the first several years of life in the United States. Family environments are all important in the first several years of a child's life, when they are developing most rapidly and have limited autonomy from family, yet family incomes tend to be the lowest in these early years of family development. We describe an ongoing experimental study of income effects on infants and toddlers.